Dual Phase Evolution - Green, David G.; Liu, Jing.; Abbass, Hussein A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This book explains how dual phase evolution operates in all these settings and provides a detailed treatment of the subject. The authors discuss the theoretical foundations for the theory, how it relates to other phase transition phenomena and its advantages in evolutionary computation and complex adaptive systems. The book provides methods and techniques to use this concept for problem solving. Dual phase evolution concerns systems that evolve via repeated phase shifts in the connectivity of their elements. It occurs in vast range of settings, including natural systems (species evolution, landscape ecology, geomorphology), socio-economic systems (social networks) and in artificial systems (annealing, evolutionary computing).
Dual Phase Evolution -- Network Theory -- Problem Solving and Evolutionary Computation -- DPE for Network Generation -- DPE Networks and Evolutionary Dynamics -- DPE for Problem Solving -- Conclusion and Future Work.
Keywords: Engineering; Computer network architectures; Physics; Engineering mathematics; Engineering; Appl.Mathematics/Computational Methods of Engineering; Complexity; Computer Systems Organization and Communication Networks